EFEKTIVITAS JUS JAMBU BIJI TERHADAP PERUBAHAN KADAR HB PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS BACEM KABUPATEN BLITAR TAHUN 2015 - Dhita Kris Prasetyanti; Lia Eforia Asmarani Ayu Putri (STRADA : Jurnal Ilmiah Kesehatan, 2017)
Based on data the number of pregnant women suffer from anemia as much as 19,4%. The goal of this research is to know the effectiveness guava juice toward the changing of Hb level among pregnant mothers in the third semester. The research design is quasi experiment.The population are all of the pregnant women in third semester with 43 mothers. By using purposive sampling technique, it was got 32 respondents. The data were analyzed by T-test dependent and T-test independent. The result of this research showed that there is difference Hb level with significance value (2-tailed) 0.00 < 0.05. After intervention the increasing of Hb level in control group is 0.5 gr/dl , while in treatment group the average increasing is 1.04 gr/dl. The difference of Hb level in average is 0.5438 gr/dl. Suggested for the pregnant mothers who consuming Fe tablet, they also should consume guava juice so the absorption of iron can be optimal.